Analysis of fixed effects for the performance test traits of the Hungarian pigs - Nagy, István; Farkas, János; Nagyé Kiszlinger, Henrietta; Bokor, Árpád (Acta Agraria Kaposváriensis, 2010)
Authors jointly analyzed station field and slaughterhouse datasets (collected and owned by the National Institute for Agricultural Quality Control between 2004.01.01 and 2009.04.30) of the Hungarian Large White, Hungarian Landrace pigs and their cross. Number of records were 5 396, 193 813) and 13 165 for station, field and slaughterhouse tests, respectively. Using multi-trait animal models the magnitude of the most important fixed effects (sex, genotype, herd, station, slaughterhouse and operator) were estimated for proportion of the valuable cuts (station test), days of test (station test), age at the end of the field test and lean meat percentage (field-slaughterhouse test), respectively. Most fixed effects were substantial except for genotype and sex which were negligible and small respectively.
Keywords: fixed effects; BLUP; pig; performance tests